In vivo NMR studies of regional cerebral energetics in MPTP model of Parkinson's disease: recovery of cerebral metabolism with acute levodopa treatment. (16th September 2013) - Bagga, Puneet; Chugani, Anup N.; Varadarajan, Komanduri S.; Patel, Anant B.
Abstract In this study, we have evaluated cerebral atrophy, neurometabolite homeostasis, and neural energetics in 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridin (MPTP) model of Parkinson's disease. In addition, the efficacy of acute l‐DOPA treatment for the reversal of altered metabolic functions was also evaluated. Cerebral atrophy and neurochemical profile were monitored in vivo using MRI and 1H MR Spectroscopy. Cerebral energetics was studied by 1H‐[13C]‐NMR spectroscopy in conjunction with infusion of 13C labeled [1, 6‐13C2]glucose or [2‐13C]acetate. MPTP treatment led to reduction in paw grip strength and increased level of GABA and myo‐inositol in striatum and olfactory bulb. 13C Labeling of glutamate‐C4 (1.93 ± 0.24 vs. 1.48 ± 0.06 μmol/g), GABA‐C2 (0.24 ± 0.04 vs. 0.18 ± 0.02 μmol/g) and glutamaine‐C4 (0.26 ± 0.04 vs. 0.20 ± 0.04 μmol/g) from [1, 6‐13C2]glucose was found to be decreased with MPTP exposure in striatum as well as in other brain regions. However, glutamine‐C4 labeling from [2‐13C]acetate was found to be increased in the striatum of the MPTP‐treated mice. Acute l‐DOPA treatment failed to normalize the increased ventricular size and level of metabolites but recovered the paw grip strength and 13C labeling of amino acids from [1, 6‐13C2]glucose and [2‐13C]acetate in MPTP‐treated mice. These data indicate that brain energy metabolism is impaired in Parkinson's disease and acute l‐DOPA therapy could temporarily recover the cerebral metabolism. <boxed-text content-type="graphic" id="jnc12407-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Cerebral atrophy, neurometabolite homeostasis, and neural energetics have been evaluated in an MPTP model of Parkinson's disease using MRI, in vivo1H MRS and 1H‐[13C]‐NMR spectroscopy, respectively. MPTP treatment led to reduced paw grip strength and neuronal function. Acute Levodopa treatment was able to recover the diminished motor function and cerebral function. CMRGlc, Cerebral metabolic rate of glucose oxidation; MPTP, 1‐Methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridin.